Update on the Mechanism of Action of Intravesical BCG Therapy to Treat Non-Muscle-Invasive Bladder Cancer - Mohamad Abou Chakra; Yi Luo; Igor Duquesne; Michael A O'Donnell (Frontiers in Bioscience-Landmark, 2024)
While more than four decades have elapsed since intravesical Bacillus Calmette-Guérin (BCG) was first used to manage non-muscle invasive bladder cancer (NMIBC), its precise mechanism of anti-tumor action remains incompletely understood. Besides the classic theory that BCG induces local (within the bladder) innate and adaptive immunity through interaction with multiple immune cells, three new concepts have emerged in the past few years that help explain the variable response to BCG therapy between patients. First, BCG has been found to directly interact and become internalized within cancer cells, inducing them to act as antigen-presenting cells (APCs) for T-cells while releasing multiple cytokines. Second, BCG has a direct cytotoxic effect on cancer cells by inducing apoptosis through caspase-dependent pathways, causing cell cycle arrest, releasing proteases from mitochondria, and inducing reactive oxygen species-mediated cell injury. Third, BCG can increase the expression of programmed death ligand 1 (PD-L1) on both cancer and infiltrating inflammatory cells to impair the cell-mediated immune response. Current data has shown that high-grade recurrence after BCG therapy is related to CD8+ T-cell anergy or ‘exhaustion’. High-field cancerization and subsequently higher neoantigen presentation to T-cells are also associated with this anergy. This may explain why BCG therapy stops working after a certain time in many patients. This review summarizes the detailed immunologic reactions associated with BCG therapy and the role of immune cell subsets in this process. Moreover, this improved mechanistic understanding suggests new strategies for enhancing the anti-tumor efficacy of BCG for future clinical benefit.